Tantangan Pendidikan Inklusi Berdasarkan Peraturan Perundangan Di Indonesia - Siti Nurhadipa; Pradika Lilia Ratna; Nisa Ulhasanah; Opi Andriani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Inclusive Education is one of the government's programs to realize justice in education. Inclusive education is a form of realizing equal distribution of education without discrimination, both children with special needs and normal children can receive the same education. This research method uses literature studies sourced from books, journals and others. The aim of this research is to find out the challenges faced, among others. ; lack of skills and attitudes of teachers in dealing with special needs children, limited facilities and infrastructure as well as low awareness of parents and the community regarding the rights of children with special needs.